The St. Martin's Guide to Writing - B. Axelrod Rise (Bedford, 2008)
The best-selling college rhetoric for over 20 years, The St. Martin's Guide has an unparalleled record of proven success. From the beginning, Axelrod and Cooper have taken the best of classic and contemporary theory, filtered it through their own and their colleagues' classroom experience, and then blended the result into a flexible classroom tool. Their step-by-step guides to writing specific kinds of essays were a groundbreaking concept and changed the way writing is taught in American colleges. The course continues to change, and Axelrod and Cooper continue to innovate: source-based writing, analysis of argument, online teaching, and visual rhetoric are some of the focuses of this latest revision. By seamlessly incorporating practical, class-tested solutions to these new challenges, Axelrod and Cooper have once again provided the best foundation for college writing.